The Effect of Financial Literacy on the Financial Management of Indigenous Papuan Traders in the Traditional Market of Sorong City - Fensca Fenolisa Lahallo; Frits Gerit John Rupilele (Transpublika Publisher, 2025)
Indigenous Papuan merchant mothers, the backbone of the family economy, often face limitations in financial knowledge and skills. This is reflected in simple financial management patterns, such as not separating personal and business finances, minimal budget planning, and low saving or investment awareness. Many are trapped in financial stagnation or losses due to poor understanding of income management, expense control, and economic risk strategies, hindering business continuity and daily needs fulfillment. This research examines the influence of financial literacy on the financial management of native Papuan women traders in Sorong City's Traditional Market. A mixed-method approach was used, combining quantitative surveys with qualitative techniques. Data collection involved observation, interviews, and questionnaires from a sample of 157 traders. The findings show that having knowledge in finance positively impacts how one manages their finances. This is supported by a t-value of 15.873, indicating a strong correlation. Additionally, with a significance level of 0.000 and an R Square of 0.619, it can be concluded that financial literacy accounts for 61.9% of the variability in financial management, while the remaining 38.1% is attributed to other factors. The study revealed that most traders do not keep financial records despite a moderate-to-high understanding of saving. Management relies on memory due to uncertain income, and the lack of separation between business and household finances remains a major obstacle. Thus, financial literacy is vital for better financial management. However, training remains essential, focusing on simple financial recording and separating business from household finances.